The Influence of Audio Visual Media on Student Learning Outcomes Sub Theme 1 Learning Weather Conditions 1 Grade III SD 097320 Serapuh T.A 2023/2024 - Andre Dame Gultom; Rio Parsaoran Napitupulu; Radode Kristianto Simarmata (MultiTech Publisher, 2023)
This research aims to determine the influence of audio visual media on student learning outcomes, Sub Theme 1 Weather Conditions Learning 1 Class III SD Negeri 097320 Serapuh T.A 2023/2024, the method in this research is a quantitative experimental type method whose research design is Pre-experimental type one pretest-posttest group. Conducted in October 2023, the population in this research was class III students at SD Negeri 097320 Serapuh for the 2023/2024 academic year with two research variables: the dependent variable (x) in the form of learning outcomes, and the independent variable (y) in the form of Audio Visual media, media Audio-visual is a combination of audio media and visual media or usually called hearing-view media which makes the presentation of learning theme content more complete. The data collection technique is a test technique with validity testing. Test results using the Normality Test, Homogeneity Test and N-Gain Test with the help of the SPSS version 23 programs, based on the calculation results, the average value (mean) was 66.5405. Which means that there is an influence of the use of the Audio Visual media model on student learning outcomes Sub Theme 1 Weather Conditions Learning 1 Class III State Elementary School 097320 Serapuh T.A 2023/2024.